Solventes eutéticos profundos: preparo, caracterização, extração e análise in vitro da bioatividade dos extratos de Pterocaulon polystachyum - Rodrigues, Victor Hugo Silva (2024)
Deep eutectic solvents (DES) are a new class of green and sustainable solvents, formed by mixing an organic salt with a hydrogen donor compound, standing out as a sustainable alternative for application in extraction processes. This study proposes the use of DES for the extraction of bioactive compounds (coumarins and phenolics) from Pterocaulon polystachyum, aiming for the ideal extraction condition regarding the compounds with high added value. Eight different DES were screened as potential solvents and were prepared and characterized in terms of physicochemical and thermal properties. The best solvent was selected according to the total phenolic content (TPC) and extraction optimization by single-factor experimental design was performed in terms of time, temperature, solid/liquid ratio, and type of extraction method – ultrasonic assisted extraction (UAE) or heating and stirring (HS). The best extraction conditions were 30 min, 40 ºC, S/L ratio of 1:20 and the use of UAE was beneficial for the extraction yield. Highlighted, DES formed by lactic acid, water and glycine (Lac:Gly:Wat 3:1:3) and DES formed by betaine and ethylene glycol (Bet:Et 1:3), both in molar ratios, obtained TPC results higher than water and ethanol, proving to be good alternatives to solvents traditionally used in industry. Furthermore, they were able to extract biocompounds from P. polystachyum residues from other extraction processes, reinforcing the concept of green engineering. The extracts obtained with these DES indicated coumarins in their composition by CCD analysis and, for DES Bet:Et 1:3, their toxicity was tested against HaCat, T24, U-87 and M059-J cells lines. Although the results did not indicate the inhibition of tumor cell growth, they showed potential application in cosmetic formulations, as the extracts were not toxic to HaCat cells in the range of concentrations usually tested for this purpose (up to 3 mg/mL), representing a new, simple and safe process for obtaining products that can be used without the need for purification. Additionally, a screening and selection methodology for the best solvent to extract coumarins was proposed, using the COSMO-RS predictive model applied in the COSMOtherm software, where these tools proved to be capable of representing the molecular structure of DES and predicting their densities and the solubility of the coumarin in solvents through the activity coefficient in infinite dilution, which helps to consolidate the use of predictive tools associated with DES and natural products